A case report on advanced undiagnosed secondary abdominal pregnancy - Bansal, Ashnoor; Saikia, Nabajyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Abdominal pregnancy is a rare form of ectopic pregnancy that involves implantation within the peritoneal cavity, exclusive of fallopian tubes, ovaries, broad ligament and cervix. Secondary abdominal pregnancy results from implantation of blastocyst into peritoneal cavity that was originally located elsewhere. It is associated with high maternal and fetal morbidity and mortality. Here, we have discussed about a 32 year old second gravida para one post caesarean section (last CS 2 years back) at 24+ weeks of gestation with rupture uterus with advanced secondary abdominal pregnancy with intrauterine death. Exploratory laparotomy with repair of rupture uterus with bilateral tubectomy was done.